2017
DOI: 10.1088/1361-6579/aa8e1f
|View full text |Cite
|
Sign up to set email alerts
|

High-accuracy automatic classification of Parkinsonian tremor severity using machine learning method

Abstract: These results indicate the feasibility of the proposed system as a clinical decision tool for Parkinsonian tremor-severity automatic scoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 36 publications
2
57
0
2
Order By: Relevance
“…The double integrals of the acceleration signal provides the displacement [48,49]. There are two main methods to convert the acceleration signal into displacement: time domain integration and frequency domain integration.…”
Section: Gait Event Determinationmentioning
confidence: 99%
“…The double integrals of the acceleration signal provides the displacement [48,49]. There are two main methods to convert the acceleration signal into displacement: time domain integration and frequency domain integration.…”
Section: Gait Event Determinationmentioning
confidence: 99%
“…The k was used between 5 and 10 to facilitate the generalization of the model during test phase. Previous investigations – such as Jeon et al (2017b) – have also found high accuracies using k NN algorithms. They assessed 85 PD patients to predict UPDRS results by using a wrist-watch-type wearable device for measuring tremors and found an accuracy level close to 84% for k NN and RF algorithms.…”
Section: Discussionmentioning
confidence: 74%
“…SVC has been widely used to detect tremor in PD patients. The accuracy level of its classifiers has ranged between 80 and 90% to quantify PD tremor (Alam et al, 2016;Jeon et al, 2017b). We used a radial compared to the best SVC used by Jeon et al (2017b) finding similar results.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In developing an optimal AM approach, development of tremor prediction machine‐learning models is important . At the moment, most of these models are very accurate in scaling tremor severity rather than predicting reoccurrence . Future studies should analyze different evaluation frequencies, corresponding computational costs, and tremor reduction to compare the feasibility of different AM approaches.…”
Section: Stimulation Parameter Modulation Demands Per Phenotypementioning
confidence: 99%